Overview of Complaints and Degrees of Hypertension in Hypertensive Patients in the Inpatients Room of RSI Pekajangan - Retno Karunia Dewi; Dian Kartikasari (Prosiding University Research Colloquium, 2022)
Hypertension is a condition of increasing in systolic blood pressure of more than 140 or diastolic 90. This is a disease that is one of health problem in Indonesia. One of the representations of hypertension is related to complaints that are often felt. The purpose of this study was to describe the description of complaints and the degree of hypertension in hypertensive patients at RSI Pekajangan. Type of this research is descriptive. The sample in this study was 84 samples from a population of 106 medical records of impatients with hypertension at RSI. The results showed that the age group that underwent hypertension was 33.3% in the late elderly group (56 to 65 years), the sufferers was dominated by women as much as 70.2%. The most patients occupied as housewives, with total of 44 patients. The highest complaint in hypertension patients was dizziness as much as 38.1% and the highest degree of hypertension was in the grade 2 hypertension group as many as 40 patients. Most hypertensive patients who are treated feel dizzy and are included in the grade 2 hypertension group